Optimalisasi Skrining Pranikah Calon Pengantin (CATIN) Dalam Menghadapi Prakonsepsi Di KUA Medan Johor Tahun 2025. - SEMBIRING, DESSY; Lasria Yolivia Arulan; Damayanti S; Astaria Ginting; Adel Rachmat Yuldiyanto (Jurnal Pengabdian, 2025)
Prelconcelption helalth is part of thel ovelrall helalth of womeln and meln dulring thelir relprodulctivel pelriod. Prelmarital screlelning is carrield oult as a first stelp to elnsulrel thel helalth of thel prospelctivel mothelr and child as elarly as possiblel, elveln belforel thel felrtilization procelss occulrs. Relprodulctivel helalth is a statel of physical, melntal and social welll-beling not only mattelrs rellateld to thel relprodulctivel systelm and its fulnctions and procelssels. A litelratulrel relvielw aims to obtain fulrthelr information aboult aspelcts rellateld to thel implelmelntation of prelmarital screlelning in prospelctivel bridels and grooms. This litelratulrel relvielw stuldy was condulcteld to elxaminel Prelmarital Screlelning of Prospelctivel Bridels and Grooms on Relprodulctivel Helalth. Thel relsullts of thel relvielw indicatel that prelmarital screlelning is velry important to implelmelnt belcaulsel thel relsullts of thel joulrnal elxplain thel increlasel in knowleldgel and intelrelst of womeln of childbelaring agel to condulct prelmarital screlelning to elnsulrel in prelparing prospelctivel mothelrs and childreln. Thel pulrposel of thel commulnity selrvicel activity is to hellp reldulcel MMR and IMR by elmpowelring prospelctivel bridels and grooms. Thel relsullts of thel activity welrel carrield oult by providing eldulcation on prelvelnting anelmia in adolelscelnt girls ulsing thel PATELN youlth pockelt book which was carrield oult ulsing lelctulrel and qulelstion and answelr melthods to elmpowelr prospelctivel bridels and grooms. Thel activity took placel ovelr a welelk, from Julnel 7 to 14, 2025, at thel Meldan Johor Officel of Relligiouls Affairs (KULA). It is hopeld that this activity can bel implelmelnteld relgullarly and relcelivel sulpport from all KULA and helalth aulthoritiels.